The Prevalence of Occupational Musculoskeletal Injuries Among Physiotherapists in Greater Tripoli - Keltoum Ajyar,; Aya Ezz Eldin,; Sami Mahjoub, (AlQalam Journal of Medical and Applied Sciences, 2025)
Physiotherapists are frequently exposed to occupational hazards that may result in work-related musculoskeletal disorders (WRMDs) due to repetitive tasks, awkward postures, and physically demanding techniques. Despite the growing awareness of WRMDs in healthcare professions globally, data concerning physiotherapists in Libya remains limited. This study aimed to determine the prevalence of WRMDs among physiotherapists in Greater Tripoli, identify the most commonly affected body regions, explore associated physical risk factors, and examine the coping strategies adopted by physiotherapists. A cross-sectional survey was conducted between May and October 2021. A total of 175 physiotherapists from five public hospitals and four private physiotherapy clinics in Tripoli participated by completing a self-administered Arabic questionnaire based on the modified Nordic Musculoskeletal Questionnaire (NMQ). Data were analyzed using SPSS version 12.0, with chi-square tests applied to examine associations between demographic and occupational variables and WRMDs (p < 0.05). The overall prevalence of WRMDs among respondents was 59.4%. The lower back (30%), neck (23.6%), and shoulder (19.2%) were the most frequently affected regions. The most common types of injury reported included vertebral disc disorders (23.4%) and muscle strains or tears (21.7%). Leading risk factors identified were fatigue (27.02%), repetitive tasks (16.89%), and manual therapy (18.91%). Common coping strategies included changing working positions (20.83%), reducing manual techniques (16.66%), and avoiding lifting (13.88%). WRMDs are highly prevalent among physiotherapists in Tripoli, particularly affecting general rehabilitation staff. Ergonomic interventions, increased specialization, and improved working conditions are essential to alleviate the physical burden on physiotherapists.